Correlations between the composition of liquid fraction of full-scale digestates and process conditions - Akhiar A.; Guilayn F.; Torrijos M.; Battimelli A.; Shamsuddin A.H.; Carrre H. (MDPI AG, 2023)
Agricultural robots; Anaerobic digestion; Biogas; Chemical equipment; Chemical oxygen demand; Crops; Fertilizers; Separation; Aromatic molecules; Hydraulic retention time; Liquid separation; Process condition; Process parameters; Separation process; Treatment and disposal; Waste activated sludges; Liquids